Prevention under the Affordable Care Act (ACA): has the ACA overpromised and under delivered?: Comment on "Interrelation of preventive care benefits and shared costs under the Affordable Care Act (ACA)" - Molinari, Carol (Kerman University of Medical Sciences, 2014)
This policy brief discusses preventive care benefits and cost-sharing included in health insurance provisions of the Affordable Care Act (ACA) legislation and highlights some consequences to Americans and the country in terms of healthcare costs and value.